2003
DOI: 10.1046/j.1365-2826.2003.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y (NPY) Delays the Oestrogen‐Induced Luteinizing Hormone (LH) Surge in the Ovariectomized Ewe: Further Evidence That NPY has a Predominant Negative Effect on LH Secretion in the Ewe

Abstract: Studies in rats suggest that neuropeptide Y (NPY) plays a stimulatory role in the generation of the preovulatory luteinizing hormone (LH) surge, via the Y1 receptor. We have investigated this issue using the oestradiol benzoate (EB)-treated ovariectomized (OVX) ewe which is a model for the preovulatory LH surge. A Y1 receptor antagonist (BIBO3304) was infused (25 microg/h) into the third cerebral ventricle (III-V) from 2 h before EB injection for 24 h, and had no effect on the ensuing LH surge. Using in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
3
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 85 publications
(110 reference statements)
4
33
3
2
Order By: Relevance
“…Other studies showed that TCDD distributed at the CNS exerts neurotoxicological effects: a high TCDD dose (10 mg/kg) administered to rats was shown to reduce LH secretion and the number of ova at ovulation (Petroff et al 2001). Exposure to TCDD at 15 mg/kg was reported to decrease the neuropeptide Y level in the arcuate nucleus (Fetissov et al 2004) that is presumably involved in ovulation (Estrada et al 2003) and the sexual maturation of the hypothalamus (Kalra & Kalra 2004). We reported in our previous study ) that the in utero and lactational exposure of rat dams to TCDD resulted in the alteration of the N-methyl-D-aspartate (NMDA) receptor subunit mRNA expression in the brain of their offspring.…”
Section: Figurementioning
confidence: 99%
“…Other studies showed that TCDD distributed at the CNS exerts neurotoxicological effects: a high TCDD dose (10 mg/kg) administered to rats was shown to reduce LH secretion and the number of ova at ovulation (Petroff et al 2001). Exposure to TCDD at 15 mg/kg was reported to decrease the neuropeptide Y level in the arcuate nucleus (Fetissov et al 2004) that is presumably involved in ovulation (Estrada et al 2003) and the sexual maturation of the hypothalamus (Kalra & Kalra 2004). We reported in our previous study ) that the in utero and lactational exposure of rat dams to TCDD resulted in the alteration of the N-methyl-D-aspartate (NMDA) receptor subunit mRNA expression in the brain of their offspring.…”
Section: Figurementioning
confidence: 99%
“…Neuropeptide Y (NPY) neurons are implicated in feeding behavior, energy use, and reproductive function (Xu et al, 2000). Because estrogen receptors are present on NPY neurons in vivo (Estrada et al, 2003), and in vitro (Belsham et al, 2004;Titolo et al, 2006), the feedback effects of estrogen on gonadotropin-releasing hormone (GnRH) neurons may be mediated via the NPY neuronal framework. Evidence also indicates that estrogen may play a role in the regulation of NPY synthesis (Shimizu et al, 1996;Ainslie et al, 2001;Pelletier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that E 2 S treatment might stimulate alterations in appetite and/or energy balance in fetal sheep; however, the mechanism by which this might occur is unclear. Estrogen receptors are present on AGRP and NPY neurons in vivo (17) and in vitro (3,39,40) and can have a dual effect on NPY induction in the adult female. During proestrus, E 2 stimulates NPY expression and release, which in turn contribute to the stimulation of preovulatory GnRH secretion into the hypophysial portal vessels (17).…”
Section: Neuropeptides Related To Feeding Behaviormentioning
confidence: 99%
“…Estrogen receptors are present on AGRP and NPY neurons in vivo (17) and in vitro (3,39,40) and can have a dual effect on NPY induction in the adult female. During proestrus, E 2 stimulates NPY expression and release, which in turn contribute to the stimulation of preovulatory GnRH secretion into the hypophysial portal vessels (17). Despite this stimulatory action in these pathways, chronic administration of E 2 has predominately anorectic properties (6,48) in rats and monkeys that depend on the inhibition of NPY and AGRP expression and release (6,14).…”
Section: Neuropeptides Related To Feeding Behaviormentioning
confidence: 99%